Primary Large Cell Neuroendocrine Carcinoma of the Breast, a Case Report with an Unusual Clinical Course. Issue 3 (30th March 2015) - Janosky, Maxwell; Bian, Jessica; Dhage, Shubhada; Levine, Jamie; Silverman, Joshua; Jors, Kathryn; Moy, Linda; Cangiarella, Joan; Muggia, Franco; Adams, Sylvia
Abstract: Large cell neuroendocrine carcinoma of the breast (NECB) is an extremely rare type of breast cancer; little is known about effective chemotherapies, and data on pathologic response to treatment are unavailable. We report the case of a 34‐years‐old woman with large cell NECB with initial clinical and pathologic evidence of treatment response to anthracycline‐containing neo‐adjuvant therapy. Histologic reassessment early during anthracycline chemotherapy revealed cell death with necrosis of 50% of the tumor cells seen in the biopsy specimen. After completing neo‐adjuvant chemotherapy, the patient underwent breast‐conserving surgery. Pathologic evaluation of the surgical specimen showed a partial response but margins were positive for residual carcinoma. Despite repeated neo‐adjuvant chemotherapy, radiotherapy, and surgical resection, the tumor grew rapidly between surgeries and recurred systemically. Therefore, we review the literature on large cell NECB and its treatment options.